Attachment figures in a middle childhood Romanian sample: Does parental migration for employment matter?. Issue 3 (3rd May 2020) - Brumariu, Laura E.; Diaconu-Gherasim, Loredana R.; Kerns, Kathryn A.; C. Lewis, Nicholette
ABSTRACT: This study assessed how children's choices of attachment figures are related to the quality of the parent-child relationship and parental economic migration in a Romanian sample. Two hundred and twenty-two children (n girls =130) 10-13 years of age completed the Attachment Figure Interview and a parental migration interview, and reported their attachment security with mother and father. Approximately 35.6% (n = 79) of children had mothers with a migration history and 48.7% (n = 104) of children had fathers with a migration history. Mothers, and to some extent fathers, serve as primary attachment figures. Grandparents, peers, siblings and relatives serve as secondary attachment figures in some situations. Further, children are less likely to choose mothers as primary attachment figures and show lower attachment security when their mothers rather than their fathers have a history of migration. Overall, this study provides empirical grounds to conceptualize parental migration as an attachment disruption.